Activation of epigenetic reprogramming via crotonylation overcomes resistance to EGFR-TKI therapy in lung cancer - Sihong Chen; Mengyan Zhong; Xiaoyuan Wang; Youwei Su; Yingxi Zhao; Simeng Wang; Shougeng Liu; Yongshan Zhao; Yang Zhang; Xinyu Fan; Zongang Liu; Lina Jia; et al. (Proceedings of the National Academy of Sciences, 2025)
Posttranslational modifications (PTMs) on histones play critical roles in cellular processes, including gene expression and tumorigenesis. However, the regulatory mechanisms and functional consequences of newly identified lysine acylation modifications in cancer therapy remain to be elucidated. Here, we established diverse preclinical tumor models resistant to epithelial growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) and focused on histone lysine crotonylation (Kcr), as it exhibited more pronounced alterations compared to other acylations. Next, we identified acyl-CoA synthetase short-chain family member 2 as a key regulator responsible for the resistance-associated decrease in crotonylation levels. Furthermore, integrated crotonylomic, transcriptomic, and epigenomic profiling, supplemented by gene manipulation studies, revealed that EGFR-TKI resistance resulted from transcriptional suppression of HNF1A and activation of the PI3K/AKT signaling pathway, which were regulated by reduced histone H3 lysine 56 crotonylation. Importantly, through pharmacological screening, we identified a histone decrotonylase inhibitor that enhanced EGFR-TKI sensitivity by activating epigenetic reprogramming through the selective upregulation of histone Kcr levels across multiple models in vitro and in vivo. Collectively, our findings uncover a previously unrecognized epigenetic mechanism driven by crotonylation that contributes to EGFR-TKI resistance, highlighting the potential of modulating crotonylation as a novel therapeutic strategy to enhance the efficacy of EGFR-TKIs in lung cancer.